1983
DOI: 10.1111/j.1365-2125.1983.tb02257.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine 10, 11 epoxide concentrations in epileptics on carbamazepine alone and in combination with other anticonvulsants.

Abstract: Steady state carbamazepine (CBZ) plasma concentrations were similar in 15 epileptics receiving monotherapy and in 24 patients taking CBZ in combination with one other anticonvulsant. The ratio of CBZ 10, 11-epoxide (CBZ-E) to the parent drug was significantly higher (P < 0.01) in those patients taking concomitant phenytoin (n = 9), phenobarbitone or primidone (n = 9), and valproic acid (n = 6) than in the patients receiving CBZ alone. In the monotherapy group, there was a significant correlation between CBZ-E/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
2

Year Published

1984
1984
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 14 publications
7
30
2
Order By: Relevance
“…values for saliva CBZ-E/CBZ ratios, 0.40 + 0.21 (using AUC derived data) and 0.41 ± 0.24 using all data points are similar to those reported by Mackichan et al (1981). If CBZ and CBZ-E possess equipotent anticon- Brodie et al (1983), there was no significant relationship in this study between CBZ concentration and CBZ-E/CBZ ratio and our findings have not confirmed the significant correlation between CBZ and CBZ-E concentrations reported by Rane et al (1976).…”
Section: Resultssupporting
confidence: 81%
“…values for saliva CBZ-E/CBZ ratios, 0.40 + 0.21 (using AUC derived data) and 0.41 ± 0.24 using all data points are similar to those reported by Mackichan et al (1981). If CBZ and CBZ-E possess equipotent anticon- Brodie et al (1983), there was no significant relationship in this study between CBZ concentration and CBZ-E/CBZ ratio and our findings have not confirmed the significant correlation between CBZ and CBZ-E concentrations reported by Rane et al (1976).…”
Section: Resultssupporting
confidence: 81%
“…The coadministration of valproic acid (VPA) with carbamazepine (CBZ) has been found to increase the concentration of relative to that of CBZ in patients (McKauge et al, 1981;Brodie et al, 1983;Levy et al, 1984). The epoxide, a stable metabolite of CBZ, is converted by epoxide hydrolase to a terminal trans-dihvdrodiol product (Tomson et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…CBZ is an enzyme inducer, and its own metabolism is susceptible to autoinduction after repeated administration. VPA increases the plasma concentration of the epoxide metabolite by inhibiting epoxide hydrolase, without any marked changes in the concentration of CBZ (76)(77)(78). The clinical significance of this interaction is particularly important in children, in whom concentrations of epoxide of Յ13 g/ ml have been observed, along with severe side effects such as vomiting and tiredness (79).…”
Section: Carbamazepine Coadministered With Valproatementioning
confidence: 99%